PEAR1 is a potential regulator of early hematopoiesis of human pluripotent stem cells. Issue 1 (27th November 2022) - Zhang, Shuo; Qu, Kengyuan; Lyu, Shuzhen; Hoyle, Dixie L.; Smith, Cory; Cheng, Linzhao; Cheng, Tao; Shen, Jun; Wang, Zack Z.
Abstract: Hemogenic endothelial (HE) cells are specialized endothelial cells to give rise to hematopoietic stem/progenitor cells during hematopoietic development. The underlying mechanisms that regulate endothelial‐to‐hematopoietic transition (EHT) of human HE cells are not fully understand. Here, we identified platelet endothelial aggregation receptor‐1 (PEAR1) as a novel regulator of early hematopoietic development in human pluripotent stem cells (hPSCs). We found that the expression of PEAP1 was elevated during hematopoietic development. A subpopulation of PEAR1 + cells overlapped with CD34 + CD144 + CD184 + CD73 − arterial‐type HE cells. Transcriptome analysis by RNA sequencing indicated that TAL1/SCL, GATA2, MYB, RUNX1 and other key transcription factors for hematopoietic development were mainly expressed in PEAR1 + cells, whereas the genes encoding for niche‐related signals, such as fibronectin, vitronectin, bone morphogenetic proteins and jagged1, were highly expressed in PEAR1 − cells. The isolated PEAR1 + cells exhibited significantly greater EHT capacity on endothelial niche, compared with the PEAR1 − cells. Colony‐forming unit (CFU) assays demonstrated the multilineage hematopoietic potential of PEAR1 + ‐derived hematopoietic cells. Furthermore, PEAR1 knockout in hPSCs by CRISPR/Cas9 technology revealed that the hematopoietic differentiation was impaired, resulting in decreased EHT capacity, decreased expression of hematopoietic‐related transcription factors, and increased expression of niche‐related signals. In summary, this study revealed a novel role of PEAR1 in balancing intrinsic and extrinsic signals for early hematopoietic fate decision. Abstract : platelet endothelial aggregation receptor‐1 ( PEAR1 ) is a key regulator involved in human early hematopoiesis of human pluripotent stem cells (hPSCs). PEAR1 increased progressively during endothelial and hematopoietic development and was a potential marker to enrich hemogenic endothelium (HE). Knockout of PEAR1 impaired the generation of hematopoietic progenitor cells (HPCs) from hPSCs.